(untitled) (Jurnal kesehatan komunitas (Journal of community health), 2013)
HIV (Human Immunodeficiency Virus) is the virus that causes AIDS (Acquired Immuno Deficiency Syndrome), which attacks the human immune system and weakens the body’s ability to fight against any disease. Man Sex with Men (MSM) is a heterosexual (attracted to women), but also attracted to men. One thousand sixty one of MSM were infected with HIV in by the year 2011 as many as 1.061 cases and are expected to increase significantly by 2025. In Lantera Minangkabau Foundation of West Sumatra in 2011, of the 621 MSM, 24 who nurtured found as many as 24 MSM are HIV infected with HIV. This study aims to determine the risk factors for HIV incidence in MSM communities, partners of Lantera Minangkabau Foundation of West Sumatera using analytical kuantitatif methods by with using case control study. The research sample respondents wereas 24 cases and 24 controls. Data were analyzed by univariate and bivariate with using chi square test and odds ratio. The results showed that the risk factors for HIV incidence in MSM community is sexual behavior (p = 0.009, OR 5.898 and 95% CI 1.609-20.479), while the factor of injecting drug use is not a risk factor for HIV incidence in MSM communities (p = 1.000, OR 1.571 and 95% CI 0.238-10.365). It is hoped suggest that the Foundation enhance communication, information, education (IEC) to the MSM community that nurtured and discovery of HIV cases, especially in key risk populations